Mandibular Osteitis Leading to the Diagnosis of SAPHO Syndrome - Tomohiro Kikuchi; Hiroyuki Fujii; Akifumi Fujita; Tomoko Sugiyama; Hideharu Sugimoto (Case Reports in Radiology)
Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome is a disorder characterized by pustular skin lesions and osteoarticular lesions. Mandibular involvement of SAPHO syndrome is clinically rare, and it is difficult to reach a diagnosis of SAPHO syndrome from only mandibular manifestations. This report describes the case of a 26-year-old woman who presented with mandibular osteitis. Orthopantomogram and computed tomography showed sclerotic change of the right body of the mandible with periosteal reaction without odontogenic infection, which suggested the possibility of SAPHO syndrome. Detailed medical interview found that she had a history of palmoplantar pustulosis treated at a local dermatology clinic and additional bone scintigraphy showed diffuse increased uptake in the right mandible, as well as in the sternum and the sternocostoclavicular joints. She was eventually diagnosed as having SAPHO syndrome. We should consider SAPHO syndrome when we encounter a patient with mandibular osteitis of unknown etiology.